1992
DOI: 10.1021/ma00032a026
|View full text |Cite
|
Sign up to set email alerts
|

Polymerization in lyotropic liquid crystals. 1. Phase behavior of photo-cross-linkable ethylene oxide (PEO)-dimethylsiloxane (PDMS) triblock copolymers PEO-PDMS-PEO in aqueous solution

Abstract: Binary phase diagrams of water and a linear ethylene oxide-dimethylsiloxane PEO-PDMS-PEO triblock copolymer (DPn of PEO = 19; DPn of PDMS = 16) and of a corresponding photo-cross-linkable PEO-PDMS-PEO triblock copolymer (DPn of PEO = 16; DPn of PDMS = 16) with cinnamate side groups located at the positions where the blocks had been joined are reported. Both systems form liquid-crystalline phases which were investigated by optical microscopy, differential scanning calorimetry, and small-angle X-ray scattering. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 4 publications
0
28
0
Order By: Relevance
“…On the other hand, studies of the SPE surfactants are much more limited. To the best of our knowledge, the only published results are those that addressed the binary phase behavior of triblock SPE surfactants with oxyethylene homopolymer as the A block (12,13). The Pluronic and SPE surfactants containing PEO homopolymers were found to follow the usual phase sequence of the low-molecular-weight ethoxylated fatty alcohols, progressing from the lamellar phase to the inverse hexagonal phase upon increasing temperature or decreasing the hydrophilic head group size.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, studies of the SPE surfactants are much more limited. To the best of our knowledge, the only published results are those that addressed the binary phase behavior of triblock SPE surfactants with oxyethylene homopolymer as the A block (12,13). The Pluronic and SPE surfactants containing PEO homopolymers were found to follow the usual phase sequence of the low-molecular-weight ethoxylated fatty alcohols, progressing from the lamellar phase to the inverse hexagonal phase upon increasing temperature or decreasing the hydrophilic head group size.…”
Section: Introductionmentioning
confidence: 99%
“…Self-organizing materials based on di-or triblock polymers were cross-linked in the presence of a block selective solvent by means of cinnamate dimerization for obtaining the permanent stabilization of the lyotropic mesophase 24,25) or for producing nanospheres from vesicles 26,27) . Thermotropic liquid crystalline systems have also been designed with inclusion of dimerizable chromophores of the cinnamic type as comonomer unit 28) .…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17] Previous studies have also reported the utilization of amphiphilic BCPs to prepare crosslinked hydrogels for tissue engineering applications. 18,19 Several approaches have been reported to combine PEG and PDMS; mainly through covalently linking linear PEG with linear PDMS to form a diblock copolymer, [20][21][22] end-capping linear PEG with linear PDMS to form a triblock copolymer, 23,24 and end-capping linear PDMS with linear PEG to form a triblock copolymer. 10,25,26 Other examples include a random-grafted PEG/PDMS copolymer 27 and a commercially available grafted PEG along a PDMS backbone.…”
Section: Introductionmentioning
confidence: 99%